Coordination-Induced Self-Assembly of a Dipeptide into Multifunctional Chiral Nanostructures - Min, Jiwei (Langmuir : the ACS journal of surfaces and colloids, 2022)
Short peptides could be used as chiral motifs to self-assemble into various artificial nanostructures with supramolecular or nanoscale chirality, but their applications still need to be expanded. Here, under the mediation of metal ions, the ferrocene-diphenylalanine (Fc-LFLF) peptide can self-assemble into various chiral nanostructures, including right-handed helical microflowers mediated by Cu2+, left-handed nanofibers mediated by Ag+, and right-handed nanofibers mediated by Zn2+ and Cd2+. Meanwhile, the gold nanoparticles could be mineralized and deposited on Cu2+/Fc-LFLF microflowers to form AuNPsCu2+/Fc-LFLF, which showed significantly improved catalytic activity. The Ag+ could be further mineralized on the peptide nanofibers to form AgNPs@Fc-LFLF, showing an excellent antibacterial effect. Overall, this study provides new insights into the chiral self-assembly of short peptides and demonstrates that the chiral peptide-metal assemblies may have broad prospects in the fields of biocatalysis and antimicrobials